Exploring Study Designs for Evaluation of Interventions Aimed to Reduce Occupational Diseases and Injuries - Henk F. van der Molen; Susan J. Stocks; Monique H.W. Frings-Dresen (Elsevier, 2016)
Effective interventions to reduce work-related exposures are available for many types of work-related diseases or injuries. However, knowledge of the impact of these interventions on injury or disease outcomes is scarce due to practical and methodological reasons. Study designs are considered for the evaluation of occupational health interventions on occupational disease or injury. Latency and frequency of occurrence of the health outcomes are two important features when designing an evaluation study with occupational disease or occupational injury as an outcome measure. Controlled evaluation studies-giving strong indications for an intervention effect-seem more suitable for more frequently occurring injuries or diseases. Uncontrolled evaluation time or case series studies are an option for evaluating less frequently occurring injuries or diseases. Interrupted time series offer alternatives to experimental randomized controlled trials to give an insight into the effectiveness of preventive actions in the work setting to decision and policy makers.